The effect of an intervention to improve newly qualified teachers' interpersonal style, students motivation and psychological need satisfaction in sport-based physical education - Tessier, D.; Sarrazin, P.; Ntoumanis, Nikos (Academic Press, 2010)
Recent developments in self-determination theory research in the educational setting (e.g., Reeve, Deci, & Ryan, 2004), suggest that teachers' interpersonal style should be considered as consisting of three dimensions: autonomy support, structure and interpersonal involvement. Based on this theoretical proposition, the purpose of the present study was to test the effects of a training program for three physical education newly qualified teachers on the aforementioned teachers' overt behaviors and students' psychological needs satisfaction, self-determined motivation and engagement in sport-based physical education. After a baseline period of four lessons, the teachers attended an informational session on adaptive student motivation and how to support it. The training program also included individualized guidance during the last four lessons of the cycle. Results revealed that from pre- to post-intervention: (1) teachers managed to improve their teaching style in terms of all three dimensions, and (2) students were receptive to these changes, as shown by increases in their reported need satisfaction, self-determined motivation and engagement in the class. © 2010 Elsevier Inc.